Pd/C-mediated depropargylation of propargyl ethers/amines in water - Rambabu, Dandela; Bhavani, S.; Nalivela, Kumara Swamy; Basaveswara Rao, M. V.; Pal, Manojit (Tetrahedron letters, 2013)
Propargyl ethers and amines are effectively depropargylated to the parent alcohols or amines via a C−O/C−N bond cleavage catalyzed by 10% Pd/C in water. This simple, facile, and inexpensive methodology could be utilized for the selective removal of propargyl groups from a variety of aryl ethers and amines.
Gesehen am 07.01.2022